Applying Economic Models To Analyse The Illicit Antiquities Trade From India: Pricing, Price Escalation And Predictive Analytics - Kumar Sundaresan, Vijay (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation applies comprehensive economic modeling to analyze the illicit antiquities trade from India, with a focus on price escalation patterns, provenance laundering mechanisms, and systemic market adaptation across regulatory periods. Drawing on an unprecedented dataset of 246,807 artifact-level records spanning 1920 to 2025, the study integrates auction house transactions, dealer inventories, museum acquisition records, court filings, and smuggling ledgers—including previously unexplored evidence from the key trafficking networks. For the first time, a structured five-block historical framework (1920–1950, 1950–1970, 1970–2000, 2000–2013, and 2014–2025) is applied to decode evolutionary shifts in trafficking routes, price behavior, and institutional responses to regulatory changes. The research develops a multi-stage economic model that quantifies markup across illicit supply chains, documenting how artifacts escalate from initial extraction payments of a few hundred dollars to final market valuations exceeding $250,000. Statistical analysis identifies high-risk artifacts using a predictive model that integrates provenance red flags, laundering typologies, and port route patterns. Geographic heatmaps of theft intensity, seizure locations, and acquisition clusters are overlaid with heritage site density and population data to reveal vulnerability hotspots, with just fifteen of India's 640 districts accounting for 42.3% of documented thefts. The study also conducts comparative market analysis of Cambodian and Nepalese artifacts, confirming structural similarities in laundering techniques, auction volume trends, and restitution challenges while identifying market-specific variations in price patterns and institutional responses. Network analysis reveals how trafficking organizations maintain compartmentalized structures with specialized roles, adapting to enforcement pressures through strategic reconfiguration rather than wholesale change. Institutional examination finds that museum gifts, particularly anonymous donations, contain significantly higher rates of provenance issues (46.8%) than direct purchases (19.3%), suggesting systematic exploitation of reduced scrutiny channels. Key findings expose the scale of under-regulated grey markets and the inefficacy of token repatriation in addressing the underlying economic incentives driving the trade. The research argues for forensic-level scrutiny of provenance narratives, targeted enforcement at high-risk ports and source districts, and urgent legal reforms addressing institutional accountability and academic authentication standards. This dissertation provides a replicable analytical framework for source and market countries to evaluate their exposure to illicit trafficking and design evidence-based countermeasures that address root economic causes rather than symptoms.